2011
DOI: 10.1111/j.1365-2842.2011.02232.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ambulatory and polysomnographic recording of jaw muscle activity during sleep in normal subjects

Abstract: Clinicians and investigators need a simple and reliable recording device to diagnose or monitor sleep bruxism (SB). The aim of this study was to compare recordings made with an ambulatory electromyographic telemetry recorder (TEL-EMG) with those made with standard sleep laboratory polysomnography with synchronised audio-visual recording (PSG-AV). Eight volunteer subjects without current history of tooth grinding spent one night in a sleep laboratory. Simultaneous bilateral masseter EMG recordings were made wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 32 publications
0
88
2
1
Order By: Relevance
“…These findings suggest that when EMG bursts of masticatory muscle are observed during sleep, activity such as swallowing, yawning, or body movements may influence the probability of observing oromotor activity that is non-specific to RMMA/SB during sleep in OSAH patients [12][13]. In the present study, a low association was found between SB incidence and AH (i.e., concomitant in only half the subjects), along with a low association with sleep arousal.…”
Section: Association Between Sb and Osahcontrasting
confidence: 37%
See 4 more Smart Citations
“…These findings suggest that when EMG bursts of masticatory muscle are observed during sleep, activity such as swallowing, yawning, or body movements may influence the probability of observing oromotor activity that is non-specific to RMMA/SB during sleep in OSAH patients [12][13]. In the present study, a low association was found between SB incidence and AH (i.e., concomitant in only half the subjects), along with a low association with sleep arousal.…”
Section: Association Between Sb and Osahcontrasting
confidence: 37%
“…The presence of other movements that were not specific to SB could provide an alternative explanation [9,[12][13]. SB may have co-occurred with periodic limb movements in a subgroup of individuals [27].…”
Section: Association Between Sb and Osahmentioning
confidence: 99%
See 3 more Smart Citations